Influence of Sleep Duration on Postpartum Weight Change in Black and Hispanic Women. Issue 2 (30th December 2018) - Herring, Sharon J.; Yu, Daohai; Spaeth, Andrea; Pien, Grace; Darden, Niesha; Riis, Valerie; Bersani, Veronica; Wallen, Jessica; Davey, Adam; Foster, Gary D.
Abstract : Objective: The primary purpose of this study was to examine associations of objectively measured sleep duration with weight changes in black and Hispanic mothers over the first postpartum year. Methods: Data were from 159 mothers (69% black, 32% Hispanic). Nocturnal sleep duration was assessed using wrist actigraphy at 6 weeks and 5 months post partum, examined as a continuous variable and in categories (< 7 vs. ≥ 7 hours/night, consistent with American Academy of Sleep Medicine recommendations). Body weights were abstracted from medical records in pregnancy and measured at 6 weeks, 5 months, and 12 months post partum. Outcomes included early postpartum (6 weeks to 5 months) and late postpartum (5 to 12 months) weight changes. Results: The majority of participants slept < 7 hours/night at 6 weeks (75%) and 5 months (63%) post partum. Early postpartum weight change did not differ by 6‐week sleep duration category. By contrast, adjusted average late postpartum weight gain (SE) was 1.8 (0.7) kg higher in participants sleeping < 7 hours/night at 5 months post partum compared with those sleeping ≥ 7 hours/night ( P  = 0.02). Results did not show statistically significant associations of continuous measures of sleep duration, nor of measures of sleep quality, with postpartum weight changes. Conclusions: Sleeping < 7 hours/night was associated with late postpartum weight gain in minority mothers.